Mycoplasma bovis 5'-nucleotidase is a virulence factor conferring mammary fitness in bovine mastitis. - Aga E Gelgie; Peleg Schneider; Christine Citti; Emilie Dordet-Frisoni; Barbara E Gillespie; Raúl A Almeida; Getahun E Agga; Yaa Serwaah Amoah; Nahum Y Shpigel; Oudessa Kerro Dego; Inna Lysnyansky (PLoS Pathogens)
Nucleases and 5' nucleotidase (5'-NT) play essential roles in cell biology and are often associated with bacterial virulence. In Mycoplasma spp., which have limited metabolic capacities and rely on nutrient availability, these enzymes are of significant importance for nucleotide salvage. This study explores the potential role of 2 membrane-associated lipoproteins, the major nuclease MnuA and 5'-NT, in Mycoplasma bovis mastitis. Mutants deficient in MnuA (mnuA::Tn) and in 5'-NT (0690::Tn) were identified through genome-wide transposon mutagenesis of M. bovis PG45 type strain and their fitness and virulence were assessed both in vitro, in axenic medium, and in vivo, using murine and cow mastitis models. The mnuA::Tn mutant demonstrated reduced nuclease activity, while 0690::Tn exhibited slow log-phase growth and impaired hydrolase activity towards nucleotides as well as deoxynucleotides (dAMP and dGMP). In comparison to the parent strain, the 0690::Tn mutant displayed markedly reduced fitness, as evidenced by a significant decrease or even absence in post-challenge mycoplasma counts in murine and cow mammary tissues, respectively. Moreover, the 0690::Tn mutant failed to induce mastitis in both experimental models. Conversely, the mnuA::Tn mutant induced inflammation in murine mammary glands, characterized by neutrophil infiltration and increased expression of major inflammatory genes. In cows, the mnuA::Tn was able to cause an increase in somatic cell counts in a manner comparable to the wild type, recruit neutrophils, and induce mastitis. Collectively, these findings provide complementary insights, revealing that disruption of 5'-NT significantly attenuated M. bovis pathogenicity, whereas a MnuA-deficient mutant retained the ability to cause mastitis.